Review of In Vitro Flowering Method for Tomato (Solanum Lycopersicum L.) - Dewi, Siska Citra; Prasetyo, Vincentius Riandaru; Sukweenadhi, Johan; Irawati, Fenny; Savitri, Wina Dian (IPTEK The Journal for Technology and Science, 2025)
Tomatoes are one of the most popular vegetable plants globally because of the many benefits that can be obtained from tomatoes. However, their availability is still insufficient for market demand. Therefore, researchers began to develop tissue culture methods to cope with market demand. Although there have been several studies on tomato flowering in vitro, information about this method is minimal and needs further development. In vitro flowering is a technique in tissue culture for flowering plants in vitro. One of the benefits is cultivating plants in a relatively short time under controlled conditions to prevent disease transmission between plants. Therefore, we conducted a literature study to compare the results of these studies to identify effective and efficient methods and factors that increase the in vitro flowering of tomato plants. In vitro flowering methods generally focus on flowering media, especially cytokinin types such as 6-Benzylaminopurine (BAP) and kinetin, and the concentration of those hormones, as well as light intensity used to induce flowering of tomato plants. Factors that affect in vitro flowering of tomato plants include tomato plant varieties, hormone types and concentrations, and light intensity.